Alkali Metal Complexes: Mixed Ligand Complexes of Alkali Metal salts of 1-Hydroxy Anthraquinone with Oxygen Donor Ligands - Prakash, D.; Chandra, R.; Kumar, B.; K. Gupta, Anuj (Asian Journal of Chemistry, 2010)
Complexes of alkali metals belonging to ML·nHL' type, where M = Li, Na or K, L = 1-hydroxy anthraquinone, n = 1 or 2 and HL' = acetyl acetone, benzoyl acetone, ethylacetoacetate, ethyl malonate, salicylaldehyde, o-hydroxy acetophenone and 2-hydroxyI- naphthaldehyde have been synthesised and characterised on the basis of elemental analysis, conductivity measurements and IR spectral studies.